Atlas of genitourinary pathology - MacLennan, Gregory T. (Springer, 2011)
Atlas of Genitourinary Pathology provides a single referral source for images and information concerning all pathological entities in the field of genitourinary pathology. The book contains gross photos and photomicrographs of pathologic entities, and variants of those entities, occurring in the following organs or anatomic sites: Adrenal Kidney Renal pelvis and ureter Urinary bladder Urethra Prostate Seminal vesicles Testis Spermatic cord and testicular adnexae Penis and scrotum The book is lavishly illustrated with images accompanied by text explaining the key diagnostic points, as well as features that help separate the entity from similar lesions. Images from the book are available online from the Extra Materials website. A comprehensive and authoritative work, Atlas of Genitourinary Pathology will prove essential reading for practicing pathologists and pathologists in training as well as medical students, urologists, radiation oncologists, and medical oncologists.